Obeticholic Acid-A Pharmacological and Clinical Review - Caezaan Keshvani; Jonathan Kopel; Hemant Goyal (MDPI AG, 2023)
Obeticholic acid (OCA) or 6-alpha-ethyl-chenodeoxycholic acid is a semisynthetic modified bile acid derivative that acts on the farnesoid X receptor (FXR) as an agonist with a higher potency than bile acid. The FXR is a nuclear receptor highly expressed in the liver and small intestine and regulates bile acid, cholesterol, glucose metabolism, inflammation, and apoptosis. The FXR group of bile acid receptors is currently under investigation for their potential role in the treatment of primary biliary cirrhosis (PBC), non-alcoholic steatohepatitis (NASH), and primary sclerosing cholangitis (PSC). Recent clinical studies suggest OCA may work synergistically with lipid modifying medications to further improve long-term outcomes with primary sclerosing cholangitis. Specifically, OCA can improve clinical outcomes in NASH patients with their different histological, metabolic, and biochemical issues as well as improve morbidity and mortality in patients suffering from PBC, PSC, or liver disease. This improvement is noted in both improved histological examination and reduced need for transplantation. In this review, we examine the pharmacology of OCA towards the treatment of PBC refractory and steatohepatitis (NASH). In addition, we examine future directions and applications of OCA for PBC, PSC, NASH, and NAFLD.